INDUCTIVELY COUPLED PLASMA MASS SPECTROMETRY FOR THE DETERMINATION OF 237Np IN SPENT NUCLEAR FUEL SAMPLES BY ISOTOPE DILUTION METHOD USING 239Np AS A SPIKE - JOE, KIHSOO; HAN, SUN-HO; SONG, BYUNG-CHUL; LEE, CHANG-HEON; HA, YEONG-KEONG; SONG, KYUSEOK (Nuclear engineering and technology, 2013)
A determination method for 237Np in spent nuclear fuel samples was developed using an isotope dilution method with 239Np as a spike. In this method, inductively coupled plasma mass spectrometry (ICP-MS) was taken for the 237Np instead of the previously used alpha spectrometry. 237Np and 239Np were measured by ICP-MS and gamma spectrometry, respectively. The recovery yield of 237Np in synthetic samples was 95.9±9.7% (1S, n=4). The 237Np contents in the spent fuel samples were 0.15, 0.25, and 1.06 μg/mgU and these values were compared with those from ORIGEN-2 code. A fairly good agreement between the measurements (m) and calculations (c) was obtained, giving ratios (m/c) of 0.93, 1.12 and 1.25 for the three PWR spent fuel samples with burnups of 16.7, 19.0, and 55.9 GWd/MtU, respectively.